The Application of Article 359 of the Criminal Code in the Investigation of the Death of Post-Operative Patients - HANDAYANI, I Gusti Ayu Ketut Rachmi; SEREGIG, I Ketut; PRASETYO, Teguh; GUNARDI, Ardi (Journal of Advanced Research in Law and Economics; Vol 8 No 5 (2017): JARLE Volume VIII Issue 5(27) Fall 2017, 2018)
The incident of the death of three post-operative patients in a line at Mitra Husada Pringsewu hospital, Lampung on April 5, 2016 had emerged the decline of public confidence toward hospitals, both public and private hospitals. The symptoms in the patients’ body before they died were convulsion and decreased consciousness. Based on dr. Ahmad Assegaf, Sp.An (an anesthesiologist), if post-operative impact occurs, then a person who takes responsibility is an anesthesiologist. This means that responsible for the death of these patients was the doctor who performed anesthesia before the operation. All three patients, who died after operation in Mitra Husada Pringsewu Hospital, respectively were Reyhan Mahardika suffered from varicocele; Suripto patients with tumor in the left leg calf; and Devi Pranita who performed caesarean section (sesco ciceasria). These patients underwent convulsion and decreased consciousness after operation, although the anesthesiologist had tried to save their life. Yet, these patients died. During the operation, the doctor had operated the use of SOPs (Standard Operating Procedures). Based on the information from the Chairman of IDI (Indonesian Doctors Association) and the Chairman of MKEK (Honors of Medical Ethics Assembly), they said that dr. Edi Pramono, Sp. An. as the anesthesiologist had done the right procedures in doing anesthetic injection to these patients. In the investigation process conducted by the Regional Police of Lampung, toward dr. Edi Pramono, Sp. An., he was presupposed in violation of Article 359 of the Criminal Code (KUHP) which stated ‘whoever due to his negligence has caused another person's death, will be sentenced with a maximum imprisonment of five years.’ In juridical study over Article 359 of the Criminal Code committed by the writer in the cases described above, it can be concluded that the element of ‘negligence’ as the main requirements of this article ‘is not fulfilled’. Thus, this Article applied in this case does not meet the main requirement of criminal elements which is presupposed, and the investigation process is terminated.